1996
DOI: 10.1101/gad.10.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the vestigial tail mutation demonstrates that Wnt-3a gene dosage regulates mouse axial development.

Abstract: Mice homozygous for the recessive mutation vestigial tail (v-t), which arose spontaneously on Chromosome 11, exhibit vertebral abnormalities, including loss of caudal vertebrae leading to shortening of the tail. Wnt-3a, a member of the wingless family of secreted glycoproteins, maps to the same chromosome. Embryos homozygous for a null mutation in Wnt-3a (Wnt-3a "e°) have a complete absence of tail bud development and are truncated rostral to the hindlimbs. Several lines of evidence reveal that vt is a hypomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
161
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(170 citation statements)
references
References 45 publications
(57 reference statements)
8
161
0
1
Order By: Relevance
“…Animals heterozygous for null alleles of either Wnt3a or T display kinked or shortened tail phenotypes due to haploinsufficiency (Dobrovolskaia-Zavadskaia 1927;Greco et al 1996). Examination of ordered allelic series of mutations in either Wnt3a or T demonstrates a correlation between the severity of the axial truncation and gene dosage (MacMurray and Shin 1988;Greco et al 1996) and suggests that Brachyury and Wnt3a participate in the development of the entire A-P axis. Our demonstration that T is a transcriptional target of the Wnt3a signaling pathway is consistent with this genetic data and suggest that a primary function of Wnt3a may be to tightly regulate the dosage of T during embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals heterozygous for null alleles of either Wnt3a or T display kinked or shortened tail phenotypes due to haploinsufficiency (Dobrovolskaia-Zavadskaia 1927;Greco et al 1996). Examination of ordered allelic series of mutations in either Wnt3a or T demonstrates a correlation between the severity of the axial truncation and gene dosage (MacMurray and Shin 1988;Greco et al 1996) and suggests that Brachyury and Wnt3a participate in the development of the entire A-P axis. Our demonstration that T is a transcriptional target of the Wnt3a signaling pathway is consistent with this genetic data and suggest that a primary function of Wnt3a may be to tightly regulate the dosage of T during embryogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt3a homozygous null mutant embryos lack all but the anterior-most seven to nine somites (Takada et al 1994;Greco et al 1996;Yoshikawa et al 1997). As a consequence, only the most rostral cervical vertebrae are formed.…”
mentioning
confidence: 99%
“…The Wnt signaling pathway was known to be important in the development and patterning of the skeleton since the early-mid 1990s when studies demonstrated that Wnt-3a mutations resulted in altered mouse axial development (42). A few years later it was shown that the lowdensity lipoprotein receptor-related protein 6 (Lrp6) knockout (Lrp6 -/-) mouse had developmental abnormalities that phenocopied many of the defects observed in mice carrying mutations in Wnt-3a, Wnt-1 or Wnt-7a genes (97).…”
Section: Role Of the Wnt Pathway In Bone Cell Functionmentioning
confidence: 99%
“…In the vestigial tail (vt) mouse mutant, a hypomorph of Wnt3a, caudal somites are missing (Greco et al, 1996), and oscillating expression of the Wnt target Axin2 is lost (Aulehla et al, 2003). The phenotype of Lrp6 null mutant mice with loss of caudal somites is very similar (Pinson et al, 2000).…”
Section: Dkk1 and Vertebral Developmentmentioning
confidence: 99%